ESSENTIAL OIL INCREASES LEAF NUMBER IN EXPLANTS OF WOODY SPECIES NATIVE TO SOUTHERN BRAZIL - Bianchini, Nadia Helena; Stefanel, Charlene Moro; Pavlack, Alana Silveira; Reiniger, Lia Rejane Silveira; Heinzmann, Berta Maria (Floresta, 2025)
This study evaluated the effects of Nectandra grandiflora Nees & Mart. ex Nees essential oil (EO) on various parameters related to the in vitro establishment of Eugenia involucrata DC. To this end, aliquots of EO were added to the ½ MS medium at final concentrations of 0.05, 0.075, 0.1, 0.125, 0.15, 0.175, and 0.2 µL mL-1, along with a positive control (nutritive medium) and a negative control (diluent). Individuals grown under greenhouse conditions were used as donors of explant material for E. involucrata. After 30 days of in vitro cultivation, assessments included survival, establishment, bacterial contamination, fungal contamination, phenolic oxidation, and number of leaves. Furthermore, to help interpret the observed results, the EO chemical composition was analyzed by gas chromatography. The results showed that, despite not inhibiting microbial contamination and not influencing phenolic oxidation, the EO at 0.075 μL mL-1 promoted the emergence of a greater number of leaves. At the same time, explant establishment (86.66%) did not differ statistically from the controls (p < 0.05). These results indicate that the EO has the potential to be used in the development of a biostimulant for E. involucrata explants.